Rnd3/RhoE Modulates Hypoxia-Inducible Factor 1α/Vascular Endothelial Growth Factor Signaling by Stabilizing Hypoxia-Inducible Factor 1α and Regulates Responsive Cardiac Angiogenesis - Yue, Xiaojing; Lin, Xi; Yang, Tingli; Yang, Xiangsheng; Yi, Xin; Jiang, Xuejun; Li, Xiaoyan; Li, Tianfa; Guo, Junli; Dai, Yuan; Shi, Jianjian; Wei, Lei; et al. (Hypertension (Dallas, Tex. 1979), 2016)
The insufficiency of compensatory angiogenesis in the heart of patients with hypertension contributes to heart failure transition. The hypoxia-inducible factor 1α–vascular endothelial growth factor (HIF1α–VEGF) signaling cascade controls responsive angiogenesis. One of the challenges in reprograming the insufficient angiogenesis is to achieve a sustainable tissue exposure to the proangiogenic factors, such as HIF1α stabilization. In this study, we identified Rnd3, a small Rho GTPase, as a proangiogenic factor participating in the regulation of the HIF1α–VEGF signaling cascade. Rnd3 physically interacted with and stabilized HIF1α, and consequently promoted VEGFA expression and endothelial cell tube formation. To demonstrate this proangiogenic role of Rnd3 in vivo, we generated Rnd3 knockout mice. Rnd3 haploinsufficient (Rnd3) mice were viable, yet developed dilated cardiomyopathy with heart failure after transverse aortic constriction stress. The poststress Rnd3 hearts showed significantly impaired angiogenesis and decreased HIF1α and VEGFA expression. The angiogenesis defect and heart failure phenotype were partially rescued by cobalt chloride treatment, a HIF1α stabilizer, confirming a critical role of Rnd3 in stress-responsive angiogenesis. Furthermore, we generated Rnd3 transgenic mice and demonstrated that Rnd3 overexpression in heart had a cardioprotective effect through reserved cardiac function and preserved responsive angiogenesis after pressure overload. Finally, we assessed the expression levels of Rnd3 in the human heart and detected significant downregulation of Rnd3 in patients with end-stage heart failure. We concluded that Rnd3 acted as a novel proangiogenic factor involved in cardiac responsive angiogenesis through HIF1α–VEGFA signaling promotion. Rnd3 downregulation observed in patients with heart failure may explain the insufficient compensatory angiogenesis involved in the transition to heart failure.